Keloid Scar Resistance to Intralesional Steroid Injections: Should We Look for Foreign Bodies? A Case Report - Alfurayh N; Alqahtani R; AlFada M (Dove Medical Press, 2023)
Nuha Alfurayh,1 Reem Alqahtani,2 Mohammed AlFada1 1Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2College of Medicine, King Khalid University, Abha, Saudi ArabiaCorrespondence: Nuha Alfurayh, Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi Arabia, Email Nuha.Alfurayh@gmail.comAbstract: Keloid is a challenging pathological condition characterized by abnormal scarring that extends beyond the boundaries of the original wound. Despite the available treatment options, keloid scars remain difficult to manage. This case report discusses a 10-year-old boy with a keloid scar on his neck following branchial anomaly repair surgery. The patient underwent multiple treatments, including triamcinolone injections, cryotherapy, and a pulsed dye laser session, with limited improvement. Subsequently, an X-ray and ultrasound were performed revealing the presence of metallic clips over the surgical site. To our knowledge, the effect of the presence of foreign bodies within the keloid scar on its response to treatment is not well understood yet. The findings of this case encourage performing imaging studies on post-surgical keloid scars resistant to treatment to rule out the presence of any foreign material. However, more trials to investigate the effect of the presence of foreign bodies on the treatment of keloid scar are required before it can be set as a mandatory investigation.Keywords: keloid, scar, resistance, steroid, cryotherapy, foreign bodies